REVIEW OF PUBLIC HOSPITAL BALANCE SCORECARD AND ITS APPLICABILITY TO INDONESIAN PUBLIC HOSPITALS - Saipul Arni Muhsyaf; Masaaki Aoki (Master of Management, Mataram University, 2018)
Indonesia is currently adopting the Balanced Scorecard (BSC) concept for its national health development plan. This indicates that Indonesian health institutions, including hospitals, were encouraged to apply BSC as their strategic management tool. This study is aimed to fill the literature gap by reviewing the existing international experiences regarding the Balanced Scorecard implementation in hospitals and assess its applicability in Indonesian public hospitals. By using a research method called